The Importance and Essential Function of the Level of Information about Reliability of Means of Transport - Liscak, Stefan (Communications - Scientific letters of the University of Zilina, 2001)
Increasing requirements on the operation reliability of means of transport require interdisciplinary approach. Theoretical estimations of reliability depend on the quality of information, mostly on the law of damage cumulation in the case of complicated operation strain. On the basis of the quality of the entry information about the operation reliability of means of transport, it is possible to use the theoretical considerations about reliability in the optimisation of the technological process of transportation.